Constructing a Compelling Case: Nurses' Experiences of Communicating Abuse and Neglect. (6th July 2021) - Lines, Lauren Elizabeth; Hutton, Alison; Grant, Julian Maree
Abstract : Child abuse and neglect is a complex problem that needs to be addressed through a multidisciplinary approach. Nurses internationally have frequent contact with children and are ideally placed to respond to children experiencing abuse and neglect. Nurses' roles can include reporting abuse to child protection services (CPS). This paper reports on one aspect of the findings of a qualitative study exploring Australian nurses' perceptions and experiences of keeping children safe from abuse. Specifically, this paper reports on the theme relating to nurses' experiences of communicating their concerns to CPS and the family when reporting abuse and neglect. This qualitative study was underpinned by social constructionism, with data collected through semi‐structured interviews with 21 nurses working with children in Australia. Key findings reported are: (1) being heard; (2) [feeling] disappointed, discouraged and disenfranchised; and (3) managing tensions between engagement and reporting. Nurses at times perceived that they were not taken seriously by CPS and felt powerless to enact change for children. Nurses subsequently had to decide how, and if, to discuss their report with families to mitigate negative reactions and maintain engagement. This study highlights the need for more effective multidisciplinary collaboration between nurses and CPS to promote change for children affected by abuse in Australia. 'This paper reports on… nurses' experiences of communicating their concerns to CPS and the family' Key Practitioner Messages: Nurses often perceived that they were not taken seriously by CPS and felt powerless to make a difference for children. Nurses experienced a tension between openly discussing their intention to report with families and minimising negative reactions such as disengagement and mistrust. This study highlights the need for greater collaboration between CPS and nurses to promote shared understanding and effective action to promote the wellbeing of children experiencing abuse and neglect.